INCLUSIVITY IN ISLAMIC EDUCATION AMID STUDENT DIVERSITY: A PHENOMENOLOGICAL STUDY AT MUHAMMADIYAH 9 - Ilham Cahya Hardiansyah (As-Sulthan Journal of Education, 2026)
This study examines the inclusive teaching practices of Al-Islam teachers amidst the increasing diversity of student backgrounds at SMA Muhammadiyah 9 Bekasi City. The research aims to describe and understand in depth the essential structures of teachers' experiences in implementing inclusive and adaptive attitudes without compromising the ideological identity of Muhammadiyah. A qualitative method with a phenomenological approach was employed. Data were gathered through in-depth interviews with three Al-Islam teachers of varying tenures, complemented by classroom observations and school activity documentation. Data analysis involved reduction, thematic clustering, and the extraction of essential meanings from the informants' experiences. The findings reveal that teacher inclusivity is manifested through an awareness of diversity as sunatullah, the implementation of dialogic-participatory learning strategies, and reflective efforts in addressing pedagogical challenges. This inclusivity is deeply rooted in the values of "Progressive Islam" (Islam Berkemajuan), which emphasize balance, justice, and humanity. In conclusion, the teacher's role as a moral role model and agent of a tolerant culture is pivotal in delivering moderate and relevant Islamic education within a pluralistic society. This research contributes significantly to the development of a contextualized inclusive Islamic education model within the Muhammadiyah school environment.